Conductivity in Half-filled Ionic Hubbard Model - Tung, Nguyen Danh; Tuan, Hoang Anh (Communications in Physics, 2014)
We calculate the temperature dependent conductivity in the half-filled ionic Hubbard model with an on-site Coulomb repulsion $U$ and an ionic energy $Δ$ by mean of the coherent potential approximation. It is shown that for intermediate and large \(Δ\) the largest conductivity occurs near the special value \(U = 2 Δ\) at all temperatures \(T\), for a fixed \(Δ\) the region of finite conductivity \([U_{c1}, U_{c2}]\) expands and its maximum decreases with increasing \(T\). Our results are in good agreement with those derived from the determinant quantum Monte Carlo simulation